Health workforce policy in the Russian Federation: How to overcome a shortage of physicians? - Sheiman, Igor (Frontiers in Public Health, 2022)
Russia looks for ways to overcome a shortage of physicians. Health workforce policy is focused on training an additional number of physicians. The current efforts have reduced some areas of the shortage but failed to solve the problem due to many factors that reproduce the deficit. A distorted structure of service delivery with weak primary care generates demand for outpatient specialists and hospital doctors and requires a perpetual increase in their number. The lack of long-term labor planning results in the oversupply of some specialties and the shortage of others. The regulation of post-graduate training is not enough to improve the allocation of physicians across specialties and health system sectors. We argue that an extensive increase in the number of physicians without changing their composition will hardly change the situation. A more active structural policy is required with a focus on strengthening primary care and improving planning and regulation of health workforce structure.